Organization of rRNA genes in Mycobacterium bovis BCG. - Suzuki, Y (1987)
The number of rRNA genes in Mycobacterium bovis BCG was examined by Southern hybridization of end-labeled 5S, 16S, and 23S rRNAs with BamHI, PstI, and SalI digests of M. bovis BCG DNA. Each RNA probe gave only one radioactive band with three kinds of DNA digest. These results suggest that M. bovis BCG chromosomes may carry only a minimum set of rRNA genes. Hybridization of randomly labeled rRNAs with BamHI, PstI, SalI, BglII, and PvuII digests of DNA from the same organism supported these conclusions. The 6.4-kilobase-pair SalI fragment containing the entire structural genes for both 16S and 23S rRNAs was cloned into pBR322. The cloned fragment was characterized by restriction endonuclease mapping, DNA-RNA hybridization analysis, and the R-loop technique. The results indicated that the fragments contained rRNA genes in the following order: 16S, 23S, and 5S rRNA genes. No tRNA gene was detected in the spacer region between the 16S and 23S rRNA genes, but one was found downstream of the 23S rRNA and 5S rRNA genes.